PCNA interacts with Prox1 and represses its transcriptional activity - Chen, Xiaoren (Molecular Vision, 2008)
PURPOSE: Prox1 is a transcription factor which can function either as a transcriptional activator, transcriptional repressor or a transcriptional corepressor. This paper seeks to better understand the role of protein–protein interactions in this multitude of functions. METHODS: We performed a yeast two-hybrid screen of an 11.5 day post coitum (dpc) mouse embryo cDNA library using the homeo-Prospero domain of Prox1 as bait. Computer modeling, cotransfection analysis and confocal immunolocalization were used to investigate the significance of one of the identified interactions. RESULTS: Proliferating cell nuclear antigen (PCNA) was identified as a Prox1 interacting protein. Prox1 interactions with PCNA require the PCNA interacting protein motif (PIP box), located in the Prospero domain of Prox1. Computer modeling of this interaction identified the apparent geometry of this interface which maintains the accessibility of Prox1 to DNA. Prox1 activated the chicken βB1-crystallin promoter in cotransfection tests as previously reported, while PCNA squelched this transcriptional activation. CONCLUSIONS: Since PCNA is expressed in the lens epithelium where Prox1 levels are low, while chicken βB1-crystallin expression activates in lens fibers where Prox1 expression is high and PCNA levels are low, these data suggest that Prox1-PCNA interactions may in part prevent the activation of βB1-crystallin expression in the lens epithelium.